Mindfulness Training Improves Quality of Life and Reduces Depression and Anxiety Symptoms Among Police Officers: Results From the POLICE Study—A Multicenter Randomized Controlled Trial - Trombka, Marcelo; Demarzo, Marcelo; Campos, Daniel; Antonio, Sonia B.; Cicuto, Karen; Walcher, Ana L.; García-Campayo, Javier; Schuman-Olivier, Zev; Rocha, Neusa S. (Frontiers in Psychiatry, 2021)
Background: Police officers' high-stress levels and its deleterious consequences are raising awareness to an epidemic of mental health problems and quality of life (QoL) impairment. There is a growing evidence that mindfulness-based interventions are efficacious to promote mental health and well-being among high-stress occupations. Methods: The POLICE study is a multicenter randomized controlled trial (RCT) with three assessment points (baseline, post-intervention, and 6-month follow-up) where police officers were randomized to mindfulness-based health promotion (MBHP) (n = 88) or a waiting list (n = 82). This article focuses on QoL, depression and anxiety symptoms, and religiosity outcomes. Mechanisms of change and MBHP feasibility were evaluated. Results: Significant group × time interaction was found for QoL, depression and anxiety symptoms, and non-organizational religiosity. Between-group analysis showed that MBHP group exhibited greater improvements in QoL, and depression and anxiety symptoms at both post-intervention (QoL d = 0.69 to 1.01; depression d = 0.97; anxiety d = 0.73) and 6-month follow-up (QoL d = 0.41 to 0.74; depression d = 0.60; anxiety d = 0.51), in addition to increasing non-organizational religiosity at post-intervention (d = 0.31). Changes on self-compassion mediated the relationship between group and pre-to-post changes for all QoL domains and facets. Group effect on QoL overall health facet at post-intervention was moderated by mindfulness trait and spirituality changes. Conclusion: MBHP is feasible and efficacious to improve QoL, and depression and anxiety symptoms among Brazilian officers. Results were maintained after 6 months. MBHP increased non-organizational religiosity, although the effect was not sustained 6 months later. To our knowledge, this is the first mindfulness-based intervention RCT to empirically demonstrate these effects among police officers. Self-compassion, mindfulness trait, and spirituality mechanisms of change are examined. Clinical Trial Registration:www.ClinicalTrials.gov. identifier: NCT03114605.